Comparative study on COD removal from reverse osmosis concentrate using two physicochemical combined processes. (15th March 2022) - Zhu, Shu; Cheng, Geng; Quan, Xuejun; Jiang, Ziwen; Chen, Hao; Cheng, Zhiliang; Qiu, Facheng
Abstract: Reverse osmosis concentrate (ROC) produced from landfill leachate contains a substantial fraction of refractory organics with low biodegradability that is challenging for conventional wastewater treatment methods. To achieve high-efficiency ROC degradation, two physicochemical combined processes, i.e. ceramic membrane/ozone-nanofiltration (CM/O3 +NF) and Ca(OH)2 coagulation-ceramic membrane/ozone-nanofiltration (Ca(OH)2 +CM/O3 +NF) were proposed. In this study, the removal efficiency of organic pollutants in process 1 (CM/O3 +NF) and process 2 (Ca(OH)2 +CM/O3 +NF) was investigated, respectively. The results showed that process 1 and process 2 were both sufficient to eliminate the refractory COD, the permeates have a COD lower than the requirements for discharge. But the process 2 had a better performance than that of process 1. The COD and TOC of ROC decreased from 2500 mg/L and 1050 mg/L to 20.23 mg/L and 8.26 mg/L after process 2 treatment, and the removal efficiency was 1.9% and 4.04% higher than those of process 1, respectively. In process 2, Ca(OH)2 flocculation significantly improves the oxidation effect of CM/O3, effectively shortens the oxidation time by 25%, improves the membrane flux of the ceramic membrane, and reduces the treatment cost of the ROC. Furthermore, the change of the composition of the macromolecular organics in the ROC during the treatment of process 1 and process 2 was compared and explored through analysis by UV2 54, 3D-EEM, GC-MS. The results indicated that the types of organic matter in the ROC treated by Process 2 decreased from 27 to 8, which was 5 less than that of Process 1. Ca(OH)2 flocculation in process 2 significantly reduces the content of macromolecular humic acid in ROC, especially has a good flocculation effect on lipids, aldehydes, carboxylic acids, ketones and other substances containing carbon-oxygen double bonds. At the same time, Ca(OH)2 provides an alkaline environment and strengthens the decomposition ability of alkanes, alkenes, and aromatics in ROC into more soluble by-products by CM/O3 . The remaining pollutants that are difficult to be oxidized are effectively filtered by NF. Overall, the Ca(OH)2 +CM/O3 +NF process with complementary functions has great potential in realizing effective ROC treatment. Graphical abstract: Image 1 Highlights: The COD removal of 99.21% was achieved in the Ca(OH)2 coagulation-ceramic membrane/ozone-nanofiltration process. The ability of ozone to oxidize refractory organics was enhanced via Ca (OH)2 . Removal mechanism analysis of pollutants in the reverse osmosis concentrate was conducted. The combined physiochemical process to treat reverse osmosis concentrate was an economic and viable measure.